Lipid metabolism during exercise - Ranallo, R. F.; Rhodes, E. C. (Sports Medicine, 1998)
Fat is an extremely important substrate for muscle contraction, both at rest and during exercise. Triglycerides (TGs), stored in adipose tissue and within muscle fibres, are considered to be the main source of the free fatty acids (FFAs) oxidised during exercise. It is still unclear, however, how the use of these substrates is regulated during exercise. The regulation seems to be multifactorial and includes: (i) dietary and nutritional status; (ii) hormonal milieu; (iii) exercise mode, intensity and duration; and (iv) training status. On the other hand, the mechanism for FFA transport from its storage as triglycerides in adipose tissue and muscle to its place of utilisation in heart, skeletal muscle, kidney and liver is more clearly understood. It has been determined that the plasma FFA turnover rate is sufficiently rapid to account for most of the fat metabolised during low intensity exercise (25 to 40% VO2max). However, an exercise intensity of 65% VO2max results in a slight decrease in the amount of plasma FFA uptake by muscle tissue. Other studies have found that during prolonged exercise, muscle TGs become the predominant source of energy obtained from fat. Furthermore, it is widely documented that endurance activities increase the energy utilisation from fat while sparing carbohydrate sources. For example, during exercise on a cycle ergometer, nonplasma FFAs and plasma FFAs contribute 40%, and carbohydrates 60%, of the total calculated amount of energy expenditure before exercise and vice versa after exercise (60% nonplasma and plasma FFAs and 40% carbohydrates). Although it was many years before it was fully demonstrated, fat is now known to be transported in the blood as FFA bound to the protein carrier albumin. The mobilisation of FFA is primarily a function of sympathetic nervous activity directed towards the adipocytes, or the 'fat pad'. This nervous activity can be direct or may be an effect of circulating catecholamines such as adrenaline (epinephrine). This article summarises the role of fat metabolism during exercise.